Hot spots of phytoene desaturase from rhodobacter sphaeroides influencing the desaturation of phytoene - Choi, Bo Hyun; Kim, Sung Hui; Lee, Pyung Cheon (Catalysts, 2021)
Phytoene desaturase (CrtI, E.C. 1.3.99.31) shows variable desaturation activity, thereby introducing different numbers of conjugated double bonds (CDB) into the substrate phytoene. In particular, Rhodobacter sphaeroides CrtI is known to introduce additional 6 CDBs into the phytoene with 3 CDBs, generating neurosporene with 9 CDBs. Although in-depth studies have been conducted on the function and phylogenetic evolution of CrtI, little information exists on its range of CDB-introducing capabilities. We investigated the relationship between the structure and CDBintroducing capability of CrtI. CrtI of R. sphaeroides KCTC 12085 was randomly mutagenized to produce carotenoids of different CDBs (neurosporene for 9 CDBs, lycopene for 11 CDBs, and 3,4didehydrolycopene for 13 CDBs). From six CrtI mutants producing different ratios of neurosporene/lycopene/3,4-didehydrolycopene, three amino acids (Leu163, Ala171, and Ile454) were identified that significantly determined carotenoid profiles. While the L163P mutation was responsible for producing neurosporene as a major carotenoid, A171P and I454T produced lycopene as the major product. Finally, according to the in silico model, the mutated amino acids are gathered in the membrane-binding domain of CrtI, which could distantly influence the FAD binding region and consequently the degree of desaturation in phytoene.
Keywords: CrtI; Phytoene desaturase; Random mutagenesis; Rhodobacter sphaeroides